O desenvolvimento da ética na filosofia do psíquico de Franz Brentano - Brito, Evandro Oliveira de (2012)
This thesis aims to compare two of Brentano‟s formulations regarding the notion of moral values and analyze them from the philosophy of the mind that serves as their base. I will explain in this way, how the reformulation of the notion of moral values arose from the development of descriptions of the activity of consciousness, presented (or assumed) by Brentano in the first stage of his intellectual development (1874-1892). I will explain, therefore, that moral values, as it was formulated by Brentano in the work Psychology from an empirical standpoint(1874), was the result of an Aristotelian-thomist solution aimed at solving a problem of modern epistemology. As such, the moral value would be only a moral sentiment. I will explain, however, that in The origin of the knowledge of right and wrong (1889) Brentano reformulated this notion by proposing a non-subjectivist moral epistemology, that guided by the works that made up the Descriptive psychology (1888-1892), considered the moral value analogous to a evident judgment. This thesis is supported by the assumption that the theory of moral knowledge, formulated by Franz Brentano in 1889, resulted from two specific changes. On one hand, this theory led to the concept of intentional object being abandoned, taken as the Archimedean point in the formulation of Psychology from an empirical standpoint. On the other hand, it resulted in the formulation of the concept of intentional act, presented in the context of the formulation of Descriptive psychology. The justification of this interpretive hypothesis will be presented through the following arguments: (1) I will present the Brentano‟s theory of moral knowledge, published in 1889 in the work The origin of the knowledge of right and wrong, and (2) I will describe the basic epistemological assumptions of Descriptive psychology who hold this theory of moral knowledge, characterized as conceptual reformulations made by Brentano in Psychology from an empirical standpoint. (3) This hypothesis will be supported by interpretive presentation of the incompatibility between the ethics of moral sentiment and ethics of moral knowledge. This incompatibility also will be supported by comparing the descriptions of Brentano‟s psychic act of moral feeling, present in Psychology from an empirical standpoint, and of Brentano‟s psychic act of moral knowledge characterized as preference, present in The origin of the knowledge of right and wrong. (4) My analysis will lead to the following conclusion. By abandoning the assumptions of the Psychology from an empirical standpoint, Brentano‟s theory of moral knowledge was based on the assumption that the notion of intentional act established an intrinsic and immediate relationship called the consciousness of moral‟s preference, or, the psychic phenomenon of preference. Author: Evandro Oliveira de Brito